Lex and Ius in the Period of Transformation - Ziembiński, Zygmunt (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2019)
The paper is an English translation of “Lex” a “ius” w okresie przemian by Zygmunt Ziembiński published originally in Polish in “Państwo i prawo” in 1991. The text is published as a part of a jubilee edition of the “Adam Mickiewicz University Law Review. 100th Anniversary of the Faculty of Law and Administration” devoted to the achieve-ments of the late Professors of the Faculty of Law and Administration of the Adam Mickiewicz University, Poznań.